2008
DOI: 10.1063/1.3009569
|View full text |Cite
|
Sign up to set email alerts
|

Gate-field-induced phase transitions in VO2: Monoclinic metal phase separation and switchable infrared reflections

Abstract: In a metal-oxide-semiconductor VO2 active layer under uniaxial stress, gate-field-induced phase transitions are revealed by strongly field-dependent Raman scattering and infrared reflections. A metal-insulator transition (MIT) is demonstrated by a strongly correlated monoclinic metal phase separation that percolates, thereby making the reflections switchable. In addition, the MIT occurs at a gate voltage around 3.36V, much lower than the threshold of a structural phase transition (SPT). Hence, the MIT is easil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 20 publications
5
41
0
Order By: Relevance
“…17,20 In accordance with past results, the rutile tetragonal phase is observed near 70 • C after the MIT occurs. In our Raman measurements, although the rutile tetragonal phase indicating the SPT is not observed, a significant change of crystalline structure is shown above 75 • C. Thus, the SPT temperature may be regarded as 75 • C and it may be considered that a first-order MIT in VO 2 is not a structure-driven MIT.…”
supporting
confidence: 79%
See 3 more Smart Citations
“…17,20 In accordance with past results, the rutile tetragonal phase is observed near 70 • C after the MIT occurs. In our Raman measurements, although the rutile tetragonal phase indicating the SPT is not observed, a significant change of crystalline structure is shown above 75 • C. Thus, the SPT temperature may be regarded as 75 • C and it may be considered that a first-order MIT in VO 2 is not a structure-driven MIT.…”
supporting
confidence: 79%
“…At room temperature, seven peaks regarding as the phonon modes of the monoclinic phase for VO 2 are observed. [15][16][17] The modes observed at 192, 222, 259, 308, 338, 388, and 498 cm -1 are confirmed as A g symmetry of the phonons. 16,17 The peaks at 142 and 613 cm -1 are also assigned to the B 1g and A 1g symmetric modes, respectively.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Thanks to the improvements in the quality of VO 2 thin films, there has been a growing emphasis on exploring logic and memory device applications of this intriguing phenomenon. Recent efforts on a Mott field effect transistor (MottFET) have demonstrated that VO 2 can be employed as the channel in a MottFET, and the applied external gate voltage switches the channel resistance between the insulating OFF state and the metallic ON state [4][5][6] . There are still several challenges for these so called "Mott devices" 7 , among which is a concern over the repeatability/reproducibility of the Mott transition because the properties of these materials are sensitive to oxygen vacancy concentration, strain, and other factors.…”
mentioning
confidence: 99%